2020
DOI: 10.1155/2020/8882207
|View full text |Cite
|
Sign up to set email alerts
|

Effective Connectivity Study Guiding the Neuromodulation Intervention in Figurative Language Comprehension Using Optical Neuroimaging

Abstract: The current study is aimed at establishing links between brain network examination and neural plasticity studies measured by optical neuroimaging. Sixteen healthy subjects were recruited from the University of Macau to test the Granger Prediction Estimation (GPE) method to investigate brain network connectivity during figurative language comprehension. The method is aimed at mapping significant causal relationships across language brain networks, captured by functional near-infrared spectroscopy measurements (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The behavioral results showed that identi cation-based trust was signi cantly higher than knowledgebased trust and knowledge-based trust was signi cantly higher than bounded rational trust in all trust dimensions of doctor trust and patient trust. The results of this study are consistent with the ndings of previous studies that doctors try to understand and respect patients' values, needs, and preferences (Mead & Bower, 2000), keep patients informed and involved in decision-making, and provide emotional support in the interpersonal interaction between doctors and patients (Epstein & Street, 2011) ), and the ow path from the left Broca (IFG) to the left Wernicke (MTG) was observed during the semantic integration of language, which emphasizes the relationship between IFG and higher cognitive functions, such as speech and language processing (Benedek, et al, 2014;Couto, et al, 2020). Additionally, it has been shown that IBS is found in the left IFG after dyadic interaction in real couples compared to randomly paired couples, suggesting that the left IFG is related to the processing of emotional information (Azhari et al, 2020;Ferstl et al, 2005;Schirmer et al, 2004).…”
Section: Figure 4 Behavior Results Of Doctor Trust and Patient Trustmentioning
confidence: 99%
“…The behavioral results showed that identi cation-based trust was signi cantly higher than knowledgebased trust and knowledge-based trust was signi cantly higher than bounded rational trust in all trust dimensions of doctor trust and patient trust. The results of this study are consistent with the ndings of previous studies that doctors try to understand and respect patients' values, needs, and preferences (Mead & Bower, 2000), keep patients informed and involved in decision-making, and provide emotional support in the interpersonal interaction between doctors and patients (Epstein & Street, 2011) ), and the ow path from the left Broca (IFG) to the left Wernicke (MTG) was observed during the semantic integration of language, which emphasizes the relationship between IFG and higher cognitive functions, such as speech and language processing (Benedek, et al, 2014;Couto, et al, 2020). Additionally, it has been shown that IBS is found in the left IFG after dyadic interaction in real couples compared to randomly paired couples, suggesting that the left IFG is related to the processing of emotional information (Azhari et al, 2020;Ferstl et al, 2005;Schirmer et al, 2004).…”
Section: Figure 4 Behavior Results Of Doctor Trust and Patient Trustmentioning
confidence: 99%